Construction coefficient in the settlements of Gllogoc Municipality (Republic of Kosova) - Çela Tomor; Ramadani Ibrahim (Bulletin of Geography. Socio-Economic Series)
This paper evaluates the built area within “cadastral zones” (subdivisions of municipalities) in order to identify the expansion tendencies of settlements, with the aim of contributing to preventing future uncontrolled developments. Demographic growth always needs more construction so it is important to provide a spatial analysis of land use. The paper is focused on the expansion dynamics of built areas within cadastral zones due to rapid social and economic changes. The lack of researches for the Drenica region has affected land use, which has been unplanned and not-to-standard, and has not preserved agricultural land. In the last two decades – since 1999 – there has been considerable growth in the construction sector across all of Kosovo. Although, according to the spatial plan, property owners have the right to develop and use their own property in their own best interests, these regulations do not give them the right to work outside the legal framework of the local plan itself. Land use should be in full compliance with spatial plans, both national and local. This study will contribute to the sustainable urbanisation of settlements and preservation of agricultural land. The results of the study will also help to make important decisions for built areas, in also providing necessary recommendations for steps to be taken to have a land use based on common interests.